Numerical and statistical analysis of boundary layer flow and heat transfer in hybrid nanofluid over various permeable surfaces - Yahaya, Rusya Iryanti (2024)
This thesis presents the studies on hybrid nanofluid flowover various permeable surfaces and conditions. Five different flow problems consisting of unsteady hybrid nanofluid flowpast a permeable Riga plate with thermal radiation and convective boundary condition, mixed convection hybrid nanofluid flow past a permeable non-isothermal cone and wedge with thermal radiation and convective boundary condition, hybrid nanofluid flow past a permeable biaxial stretching/shrinking surface with thermal radiation, oblique stagnation-point flow of hybrid nanofluid towards a permeable shrinking surface, and magnetohydrodynamics (MHD) stagnation-point flow of ternary hybrid nanofluid over a permeable radially shrinking disk with thermal radiation, viscous dissipation, and convective boundary condition are solved, analyzed, and discussed. The geometries and governing conditions of these flow problems are defined using partial differential equations and boundary conditions. Then, similarity transformation reduced these equations into non-linear ordinary differential equations before being solved numerically using the bvp4c solver in MATLAB. Multiple solutions are found within certain ranges of unsteadiness, mixed convection, and stretching/shrinking parameters. However, stability analysis confirms that only the first solution is stable while the others are unstable. The numerical results show that hybrid nanofluid and ternary hybrid nanofluid improve the physical quantities of interest, namely the local skin friction coefficient and Nusselt number. Nevertheless, in some cases where boundary suction is applied, hybrid nanofluids may have a lower local Nusselt number than nanofluids. Increasing the suction parameter can help compensate for this reduction in heat transfer performance. The imposition of thermal radiation and convective boundary condition also increases the local Nusselt number. Additionally, the assisting mixed convection flow exhibits a higher local skin friction coefficient and Nusselt number than the opposing flow. Finally, response surface methodology (RSM) is employed to determine the significance and optimal settings of the controlling parameters on the local Nusselt number. Generally, the highest value of the suction parameter maximizes the local Nusselt number and improves the heat transfer rate at the surface.